The study of Business Innovation Management Potential to Business Performance of Small and Medium Enterprises in Phra Nakhon Si Ayutthaya Province - Sarawut, Supawadee; Treemongkol, Patcha (Mahachula Academic Journal, 2021)
The purposes of this research were to study (1) business innovation management potential of Small and Medium Enterprises in Phra Nakhon Si Ayutthaya province (2) business performance of Small and Medium Enterprises in Phra Nakhon Si Ayutthaya province and (3) business innovation management potential to business performance of Small and Medium Enterprises in Phra Nakhon Si Ayutthaya province. The questionnaire was used to collect data from 348 owners of small and medium enterprises in Phra Nakhon Si Ayutthaya province. The statistics used for data analysis were Frequency, Percentage, Mean, Standard Deviation and Multiple Regression Analysis. The results of the study found that: (1) opinion business innovation management potential of Small and Medium Enterprises in Phra Nakhon Si Ayutthaya province at a high level ( = 3.83) (2) business business performance of Small and Medium Enterprises in Phra Nakhon Si Ayutthaya province at a high level ( = 3.82) and (3) business innovation management potential by human resources management and marketing management influence to business performance of Small and Medium Enterprises in Phra Nakhon Si Ayutthaya province.